Enhancing Senior Secondary School Students’ Academic Performance in Chemistry Through the Implementation of Think-Pair-Share Strategy - Nnoli, Juliana Nkiru (Social Education Research, 2024)
This study investigates the impact of the Think-Pair-Share (TPS) strategy on students’ academic performance in Chemistry at the Awka Education Zone, establishing its significance in addressing persistent poor performance in the subject. A quasi-experimental design was employed, with Chemistry taught to the experimental group via TPS and to the control group by traditional lecture methods. The study’s population consisted of all Chemistry students in public secondary schools within the Awka Education Zone, totalling 1,298 students, from which a sample of 120 students (60 males and 60 females) was drawn using purposive sampling and straightforward balloting. Data were collected using the Achievement in Chemistry Test, a validated instrument with a reliability factor of 0.83. Mean and standard deviation were used to analyze the research questions, while a t-test was used to examine the hypotheses. Results showed that students taught Chemistry using TPS outperformed those taught by lecture. Male students taught using TPS outperformed female students, whereas, with the lecture method, male students also outperformed female students. There was a significant difference in achievement scores between students taught with TPS and those taught with the lecture method, as well as between Male and Female Students taught with TPS. Students of all sexes did badly when taught using the lecture method. The study recommends the implementation of TPS in teaching Chemistry and calls for the provision of resources by the government to enhance its effectiveness.